Implementasi Kebijakan Penanggulangan Kemiskinan di Kabupaten Lamongan - Fahmi Anas; Siti Zulkhah; Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2024)
Poverty is still one of the main problems for developing countries, including Indonesia. Indonesia is one of the developing countries which has quite a large number of poor people and needs to be resolved and find a way out until now. Various poverty reduction programs have been continuously carried out by both the central government and regional governments. This research aims to describe and analyze the implementation of the Poverty Reduction Policy from a Political Economy Perspective in Lamongan Regency. The research results show that the implementation of the Poverty Alleviation Policy in Lamongan Regency from a Political Economy Perspective has gone quite well. the entire series of Lamongan Regency Regional Regulation Number 16 of 2021 concerning poverty alleviation, home care service programs, RTLH and HAMP. The success of the Poverty Reduction Policy is strongly supported by the Lamongan Regency Regional Government and related Regional Apparatus Organizations by prioritizing collaboration.